CoOx@Co Nanoparticle‐based Catalyst for Efficient Selective Transfer Hydrogenation of α, β‐Unsaturated Aldehydes. Issue 4 (17th December 2019) - Gong, Wanbing; Han, Miaomiao; Chen, Chun; Lin, Yue; Wang, Guozhong; Zhang, Haimin; Zhao, Huijun
Abstract: Currently, developing simple and effective catalysts for selective hydrogenation of α, β‐unsaturated aldehydes to unsaturated alcohols is challenging. Herein, an efficient CoOx ‐shell/Co‐core structured nanoparticle catalyst is synthesized by a facile ultrasonic‐assisted carbothermal reduction method. The resultant catalyst exhibits outstanding catalytic performance toward the selective transfer hydrogenation of a wide spectrum of α, β‐unsaturated aldehydes into corresponding unsaturated alcohols with over 90 % selectivity. This is the simplest nonprecious metal catalyst to be reported for the selective hydrogenation of unsaturated aldehydes. Abstract : Transfer hydrogenation : A facile ultrasonic‐assisted carbothermal reduction method is innovatively utilized to prepare core‐shell structured CoOx @Co nanoparticle catalyst as high performance selective transfer hydrogenation catalyst to convert α, β‐unsaturated aldehydes into corresponding unsaturated alcohols with over 90 % selectivity.